Hyaline fibromatosis syndrome: cutaneous manifestations - Silvio Alencar Marques; Hamilton Ometto Stolf; Juliana Ocanha Polizel; Tânia Munhoz; Marcela Calixto Brandão; Mariangela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2016)
Abstract Hyaline fibromatosis syndrome is the current name for clinical manifestations of diseases previously known as "infantile systemic hyalinosis" and "juvenile hyaline fibromatosis". The authors report representative clinical cases of each one of the above subtypes with emphasis on cutaneous manifestations and difficulties for early diagnosis in this syndrome, essentially of multidisciplinary approach.